The impacts of rainfall and soil moisture to flood hazards in a humid mountainous catchment: a modeling investigation - Yu, Tianxue; Ran, Qihua; Pan, Hailong; Li, Jiyu; Pan, Jiajia; Ye, Sheng (Frontiers in Earth Science, 2023)
Floods pose a significant threat to the safety of countries with severe societal, economic, and environmental consequences, especially the flash floods in mountainous regions. Previous studies have shown that many floods were caused by intense rainfall with highly saturated soil. In this study, we applied a physically-based distributed hydrological model (Integrated Hydrology Model, InHM) to a warm humid mountainous catchment in Southwest China, the Shouxi River. The main objective of our research is to investigate the relative importance of rainfall and antecedent soil moisture on flood generation in our study region. Our results show that an increase in rainfall return period and antecedent soil saturation ratio significantly increased peak flow and shortened peak time. There is a correlation between the ratio of antecedent soil saturation ratio to rainfall (SPR) and peak flow. When SPR < 1, there is a positive correlation; when SPR > 1, there is a negative correlation. Additionally, with the increase in drainage area, the relative importance of rainfall tends to decrease, while the relative contribution of soil saturation ratio tends to increase. The findings could provide support for the determination of the dominant factors influencing runoff generation in humid regions, offering scientific support for the timely and effective flood prevention and mitigation measures in mountainous regions.